Comparación de la ultraestructura de la cáscara del huevo de la tortuga Rhinoclemmys pulcherrima con la de los huevos de otros reptiles - Acuña Mesén, Rafael Arturo (1987)
The eggshell of the red turtle, Rhinoclemmys pulcherrima is composed of an external cuticle, amiddle calcareous layer and the internal membrane. The cuticle is not sculptured as in those of the kinosternidae. The radial view is similar in eggs of Geochelone elephantopus. The cuticle of R pulcherrima shows superficial fractures or crevices whose complementary edges are similar to a jigsaw puzzle. The calcareous layer is formed by structural units composed by groups of needle-like aragonite crystals. In the crocodilian egg, the shell shows calcite deposited in lates instead of aragonite. The calcareous units are interlocked, a situation that is not present in the shell of marine turtle eggs (Lepidochelys olivacea and Chelonia mydas). The inner extremes of the calcareous units are !U rrounded by a palisade of needle-like aragonite erysta!s. This type of stru erure is not o bserved in other reptilian eggshells.